Propuesta de mejoramiento para los indicadores de servicio en el call center de la empresa Avanzo (2021)
When identifying the problem of answering calls in the Call Center that provides the customer service for the Avanzo company, based on the information provided by the area, carry out the corresponding analyzes to identify the causes and root of the problem in order to develop and propose an improvement for the area that allows the correct performance of the process and Likewise, the quality and management indicators are standardized, guaranteeing good service to the customer that generates satisfaction and greater quality care is acquired.